Advanced Management and Monitoring Functions at the TMA 550AL Manufacturing Centre, used for ATR - Ovidiu, Moldovan; Ioan, Moga; Husi, Géza (Recent Innovations in Mechatronics, 2015)
This paper amiss to make an overview of the management and monitoring functions implemented at the TMA 550 AL flexible manufacturing system, functions that are used to implement the automatic tool readjustment function.